Rebuilding Lives and Communities Postdisaster: A Case Study on Migrant Workers and Diversity in the USA. Issue 4 (2nd October 2018) - Drolet, Julie; Ersing, Robin; Dominelli, Lena; Alston, Margaret; Mathbor, Golam; Huang, Yenyi; Wu, Haorui
ABSTRACT: There is a need to better understand long-term disaster recovery and reconstruction challenges in diverse communities. This case study was part of a larger study undertaken by the Rebuilding Lives Post-Disaster research partnership, where field research was conducted in disaster-affected communities in Canada, the USA, Australia, India, Pakistan, and Taiwan. The objective of this exploratory case study was to focus on experiences of affected migrant workers from diverse communities in Florida, USA, in relation to long-term disaster recovery and reconstruction work following hurricanes, to ensure that lessons learned from these experiences could inform best practices and policy. The study focused particularly on the role of community processes and dynamics in shaping postdisaster recovery. Qualitative research explored diverse experiences of participants through interviews with government officials, community leaders, and disaster responders. The study found that migrant workers faced challenges due to the lack of consideration with regard to immigration status, linguistic, and cultural needs in disaster recovery. IMPLICATIONS Disaster recovery processes need to consider the diversity of affected populations to ensure assistance and responses meet the differing needs of all community members in postdisaster recovery. All members of diverse communities should be included in disaster response and longer-term recovery efforts. Social workers can assist in ensuring that diversity is a consideration in disaster and emergency management.